DIPG-15. POLYAMINE PATHWAY INHIBITION IS A POTENT NOVEL THERAPEUTIC STRATEGY AGAINST DIFFUSE INTRINSIC PONTINE GLIOMA. (4th December 2020) - Khan, Aaminah; Gamble, Laura; Upton, Dannielle; Yu, Denise; Ehteda, Anahid; Pandher, Ruby; Mayoh, Chelsea; Burns, Mark; Norris, Murray; Haber, Michelle; Tsoli, Maria; Ziegler, David
Abstract: DIPG is an aggressive paediatric brainstem tumour, with a median survival of less than 1 year. Polyamines are intracellular polycations that control important aspects of cell growth and are often upregulated in cancer. Difluoromethylornithine (DFMO) is an FDA-approved inhibitor of the enzyme ornithine decarboxylase (ODC1) which is a key driver of polyamine synthesis. We investigated the efficacy of polyamine pathway inhibitors as a therapeutic strategy against DIPG. We found high expression levels of synthetic enzymes in the polyamine pathway in primary patient samples and cultures. Using cytotoxicity and clonogenic assays, we found that DFMO inhibited the proliferation of DIPG neurospheres. However, DIPG cells compensated for DFMO inhibition by increasing expression of the polyamine transporter SLC3A2. Gene expression analysis showed that the polyamine transporter, SLC3A2, was significantly overexpressed in DIPG compared with all other high-risk childhood cancers. Addition of polyamine transporter inhibitor AMXT 1501 to DFMO led to synergistic inhibition of DIPG proliferation. Consistent with the in vitro results, the combination treatment significantly prolonged the survival of mice bearing 3 different DIPG orthografts with 2/3 of the animals surviving up to 160 days. Addition of irradiation further improved the survival of mice treated with DFMO and AMXT 1501. Our results suggest that DIPG tumours are exquisitely sensitive to polyamine inhibitors and that dual blockade of polyamine synthesis and transport is a promising novel therapeutic strategy. AMXT 1501 is currently in clinical development for adult cancers (NCT03536728). A clinical trial for DIPG patients is planned through the CONNECT consortium.